#### Answer

$\sqrt{\dfrac{18x^{4}y^{6}}{3z}}=\dfrac{6x^{2}y^{3}}{\sqrt{6z}}$

#### Work Step by Step

$\sqrt{\dfrac{18x^{4}y^{6}}{3z}}$
Rewrite this expression as $\dfrac{\sqrt{9\cdot2(x^{4}y^6)}}{\sqrt{3z}}$ and simplify it:
$\sqrt{\dfrac{18x^{4}y^{6}}{3z}}=\dfrac{\sqrt{9\cdot2(x^{4}y^6)}}{\sqrt{3z}}=\dfrac{3x^{2}y^{3}\sqrt{2}}{\sqrt{3z}}=...$
Multiply this fraction by $\dfrac{\sqrt{2}}{\sqrt{2}}$ and simplify again if possible:
$...=\dfrac{3x^{2}y^{3}\sqrt{2}}{\sqrt{3z}}\cdot\dfrac{\sqrt{2}}{\sqrt{2}}=\dfrac{3x^{2}y^{3}\sqrt{2^{2}}}{\sqrt{6z}}=\dfrac{3x^{2}y^{3}(2)}{\sqrt{6z}}=\dfrac{6x^{2}y^{3}}{\sqrt{6z}}$